2019
DOI: 10.1021/acssuschemeng.8b06677
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine: An Amine Oxidase Mimicking Sustainable Catalyst for the Synthesis of Nitrogen Heterocycles under Aqueous Conditions

Abstract: The catalytic activity of polydopamine (PDA) as an amine oxidase mimic is demonstrated under aqueous conditions for the synthesis of benzimidazoles, quinoxalines, quinazolinones and oxidation of secondary amines. The synthesis occurs through activation of the amines by the catechol-quinone moieties of PDA, followed by transamination and an oxidative cyclization of these benzylic (or) arylethyl imine adducts with o-phenylenediamines and 2-aminobenzamides akin to the amine oxidase enzymes in the presence of beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…27 Several metal-free approaches with graphene oxide (GO), 28 reduced graphene oxide (rGO), 29 mesoporous graphitic carbon nitride (mpg-C 3 N 4 ), 30 polymaleimide, 31 and polydopamine have been published as well. 32 Interestingly, Hayashi and co-workers published several convincing reports where they used untreated ACs to synthesize anthracenes, pyridines, pyrazoles and indoles under mild oxidative conditions. 11,[33][34][35][36] Furthermore, they demonstrated that untreated AC delivers higher yields of quinolines and isoquinolines than Pd/C in MeCN.…”
Section: Introductionmentioning
confidence: 99%
“…27 Several metal-free approaches with graphene oxide (GO), 28 reduced graphene oxide (rGO), 29 mesoporous graphitic carbon nitride (mpg-C 3 N 4 ), 30 polymaleimide, 31 and polydopamine have been published as well. 32 Interestingly, Hayashi and co-workers published several convincing reports where they used untreated ACs to synthesize anthracenes, pyridines, pyrazoles and indoles under mild oxidative conditions. 11,[33][34][35][36] Furthermore, they demonstrated that untreated AC delivers higher yields of quinolines and isoquinolines than Pd/C in MeCN.…”
Section: Introductionmentioning
confidence: 99%
“…2‐(3,4,5‐Trimethoxyphenyl)‐1H‐benzoimidazole (7 j) [29] Yield (219 mg, 77 % yield, white solid), m.p. 257 – 259 °C.…”
Section: Methodsmentioning
confidence: 99%
“…110 Recently, the catalytic activity of PDA as an amine oxidase mimic has been reported for the synthesis of benzimidazoles, quinoxalines, quinazolinones and oxidation of secondary amines. 111 Different from supporting material for metallic catalyst, PDA cannot be considered as an inert component or coating as it can generate reactivity. Generally, PDA itself as catalyst has been less explored compared to PDA supported metallic catalyst especially in the form of nanoreactors.…”
Section: Pda As a Direct Catalystmentioning
confidence: 99%